A remark on the disputes and contentions in this province - Frielinghuysen, Theodorus, 1723-approximately 1761 ([publisher not identified], 1755)
Reaction of a pastor of the Reformed Church to the denial of a charter and sum of money by the Church of England for the establishment of a college or seminary to be built in New York.